Review of the Lutrochidae (Coleoptera) of the Guianas and Lesser Antilles, with description of four new species - Maier, Crystal A.; Short, Andrew Edward Z. (Zootaxa, 2014)
The species of Lutrochidae from the Guianas, and the Lesser Antilles are reviewed, including the first reports of the family from Guyana, Suriname, and Grenada. Four species are described as new: Lutrochus funkae n. sp. and L. wao n. sp. from Guyana and French Guiana, L. grenadensis n. sp. from Grenada, and L. leeanneae n. sp. from Suriname. Photographs, genitalia illustrations, and distribution maps are provided for all species, and habitat photos and notes are presented for the species for which they are available.